Vitamin D Deficiency And Insufficiency In Turkish Patients With Breast Cancer - Kayali, F. İlknur and Habiboğlu, Rahşan and Sarıcanbaz, İrem (Progress in Nutrition, 2021)
Aim: We aimed to reveal vitamin D levels in women with breast cancer. Patients and Methods: 561 women with primary breast cancer were included in the study. The median age was 55.86 years (between 20 – 78 years). All of the patients were treated with curative intend. None of the patients had metastatic disease. Results: The median 25(OH)D level was 11.92ng/ml and the mean 25(OH)D level was 13.91ng/ml . Deficiency was detected in 456 patients (81.28%) and insufficiency was detected in 61 patients (10.87 %). Conclusion:This study points out that vitamin D levels in breast cancer patients should be measured and be corrected whenever diagnosed.